Assessment of progress and competence in tonsillectomy surgery using cumulative sum analysis. Issue 8 (12th July 2018) - Abou-Foul, A K; Taghi, A; Tolley, N S; Awad, Z
Abstract: Objective: To assess the feasibility of using cumulative sum analysis to show trainees' performance curves and highlight concerns in tonsillectomy surgery. Methods: In this prospective study, the performance of eight otolaryngology trainees (in their first 6–12 months in the specialty) was compared to that of experts (over 150 tonsillectomies performed) in terms of operative time and post-operative complications. Cumulative sum analysis curves were generated to highlight trainees' performance, and were updated after each performance. Results: The average operative time was 23 minutes (standard deviation = 11) for experts and 38 minutes (standard deviation = 16) for trainees ( p < 0.0001). Cumulative sum analysis charts for trainees' operative time initially rose and then started to plateau after a number of cases (range, 25–30), while that of experts remained low. Cumulative sum analysis charts for complications can be used to monitor performance. In this study, complications were combined (because of low incidence) to allow use of this outcome measure. Conclusion: The flexibility of the cumulative sum analysis makes it adaptable to any outcome. It is a strong adjunct in surgical training to monitor progress and competence. Its sensitivity also allows early detection of poor performance, to instigate intervention.